Effects of High Frequency Acceleration Device on Aligner Treatment-A Pilot Study - Thomas S. Shipley (MDPI AG, 2018)
Evaluation of the effect of a high frequency acceleration device (HFA) on clear aligner exchange intervals and treatment time required to achieve prescribed tooth movements. Sixteen subjects with similar Class I malocclusions, ≤5 mm crowding, and treated with aligner orthodontic therapy (Invisalign) were divided into two groups. Group 1 (experimental; n = 8) underwent aligner treatment in conjunction with daily use of the HFA device and exchanged aligners every five days. Group 2 (controls; n = 8) underwent aligner treatment without use of the device and exchanged aligners every 14 days according to the manufacturer’s recommended interval. All subjects were treated by one investigator, and results—total number of aligners used, and number of refinements required—were evaluated by both prior to final mobile retention (Vivera) scan. A significant decrease in both treatment time and number of aligners required to complete treatment was observed by HFA subjects vs. controls. In addition, no refinements were required by HFA subjects, whereas six of eight control subjects required one or more refinements. The results of the present preliminary report showed that the use of the HFA device in conjunction with aligner orthodontic treatment resulted in a significant decrease in the length of treatment. Moreover, the number of patients requiring refining treatment was significantly lower.